Komitmen Organisasi dan Prosocial Behavior Sebagai Pemoderasi Kompetensi Aparatur Terhadap Akuntabilitas Pengelolaan Dana Desa - Wibawa, Dewa Made Ananta Satria; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p02, 2022)
This study aims to examine organizational commitment and prosocial behavior as a moderator of the influence of apparatus competence on the accountability of village fund management in Tabanan Regency. The data source is primary data collected through questionnaires distributed in 133 villages in Tabanan Regency. The sampling method used was cluster random sampling with the village head, village secretary, and village treasurer as respondents, totaling 108 people. The data analysis used in this research is Path Analysis (SEM-PLS). This study found that the competence of the apparatus had a positive and significant effect on the accountability of village fund management. The results of the moderating effect test, this study found that organizational commitment was able to strengthen the influence of apparatus competence on the accountability of village fund management received and prosocial behavior was able to strengthen the influence of apparatus competence on the accountability of village fund management received.              Keywords: Commitment; Prosocial Behavior; Competence; Accountability.